2016
DOI: 10.1016/j.aninu.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant systems in chick embryo development. Part 1. Vitamin E, carotenoids and selenium

Abstract: Chick viability is known to be an important factor determining profitability of the poultry industry. Chick embryo tissues contain a high proportion of highly polyunsaturated fatty acids in the lipid fraction and therefore need antioxidant defence. The antioxidant system of the developing embryo and newly hatched chick includes the antioxidant enzymes (superoxide dismutase, glutathione peroxidase, catalase), water-soluble antioxidants (ascorbic acid, taurine, carnitine, glutathione, etc.), fat-soluble antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 111 publications
2
111
2
1
Order By: Relevance
“…The accumulation and concentration of lipid-soluble antioxidants in embryonic tissues may have adaptive significance in providing protection to PUFAs against peroxidation, particularly at hatching (Surai, 2002). It has been reported that large amounts of vitamin E accumulation may occur with a high PUFA in the lipid fraction of brain; therefore, lipids play an important role in vitamin E solubilisation and subsequent absorption (Surai, 2002;Surai et al, 2016). This observation was confirmed by Schaal (2008), who concluded that chicks injected with vitamin E had increased relative brain weight and brain total lipid level to protect lipid membranes from the harmful effects of radical oxygen species and allow for increased lipid utilisation for energy production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accumulation and concentration of lipid-soluble antioxidants in embryonic tissues may have adaptive significance in providing protection to PUFAs against peroxidation, particularly at hatching (Surai, 2002). It has been reported that large amounts of vitamin E accumulation may occur with a high PUFA in the lipid fraction of brain; therefore, lipids play an important role in vitamin E solubilisation and subsequent absorption (Surai, 2002;Surai et al, 2016). This observation was confirmed by Schaal (2008), who concluded that chicks injected with vitamin E had increased relative brain weight and brain total lipid level to protect lipid membranes from the harmful effects of radical oxygen species and allow for increased lipid utilisation for energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Other isomers of vitamin E are found in the egg yolk and embryonic tissues, but at much lower concentrations. Furthermore, α-tocopherol exhibits its highest biological activity during the development of the embryo (Surai et al, 2016). Ionov et al (1994) reported that the concentration of α-tocopherol in the egg yolk of quail was 252.4 µg g −1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high percentage of Indigofera zollingeriana leaf meal replace up to 11% protein soybean meal can increase the content of betacarotene in the diet of laying ducks. Carotenoids (beta carotene) provide antioxidant defenses in lipids (Surai et al, 2016). Moreover, the Sardinella lemuru fish oil rich in omega-3 fatty acids that most have double bonds so susceptible to oxidative degradation (Shahidi and Zhang, 2010).…”
mentioning
confidence: 99%